(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
An electrically-assisted microextraction method called electromembrane extraction, followed by a simple high performance liquid chromatography and ultraviolet detection was developed and validated for determining phenobarbital in biological samples. The major parameters influencing the electromembrane extraction procedure including solvent composition, voltage, pH of acceptor and donor solutions, salt effect, and time of extraction were evaluated and optimized. The drug was extracted from the donor aqueous sample solution (pH 9) to the acceptor aqueous solution (pH 13). The donor and acceptor phases were separated by a hollow fiber dipped in 1-octanol as a supported liquid membrane. A voltage of 40 V during 20 minutes was applied as the driving force. The enrichment factor was obtained >51 which enhanced the sensitivity of the instrument. Limit of detection and limit of quantitation were 7.5 and 25 ng/ mL, respectively. The method was linear over the range of 25-1000 ng/mL for phenobarbital (R2 >0.9998) with repeatability (%RSD) between 0.4% and 6.8% (n = 3). The proposed method was successfully applied to human plasma and urine samples with relative recovery of 70-80% and %RSD < 6.8%.